REALISME MAGIS PADA NOVEL ANAK-ANAK SEMAR KARYA SHINDUNATA DALAM PERSPEKTIF PEWAYANGAN SEBAGAI SIMBOLIS BUDAYA JAWA - Puja Deasy Adelia; Trie Utari Dewi (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study focuses on the elements of magical realism and wayang as symbolic representations of Javanese culture in the novel Anak-Anak Semar by Sindhunata. The novel presents magical, mystical, and irrational imagery drawn from mythology, folklore, and legends of traditional society into the realm of modern literature. This research employs a descriptive qualitative method through the analysis of words, sentences, and narratives. The data consist of excerpts from the novel. Data collection was carried out using the note-taking observation method, by identifying excerpts of sentences found in the novel, with the aim of describing the five elements of magical realism based on Wendy B. Faris’s theory and Clifford Geertz’s theory to explore wayang as a symbol of Javanese culture. Based on this analysis, all five elements of magical realism were found to be closely linked with wayang as a symbol of Javanese culture, which appears in the form of magical narratives framed within Javanese cultural context. Through the fusion of reality and magic, the author not only presents a story rich in imagination but also reinforces cultural identity and traditional values that remain relevant in the modern context.